Beyond Responsivity: Client Service Engagement in a Reentry Demonstration Program - Sachs, Nicole M. (International journal of offender therapy and comparative criminology, 2018)
The specific responsivity principle advises us to provide offenders with treatment that takes into account their responsiveness to treatment, tied for example to their learning style, motivation, and gender. We examine challenges to service engagement and attendance in a community-based program in a reentry setting, and consider how far they correspond with these factors. Drawing on qualitative accounts of parolee engagement in services provided by parolees, service providers, case managers, and parole officers, we identify a number of difficulties faced by clients. These include logistical factors that affect clients' physical ability to enroll in or attend programming (such as documentation, employment needs, and transportation problems) as well as elements of program and service delivery (such as client-provider matching, therapeutic style, and curriculum factors). We conclude that we should look beyond responsivity and consider logistical factors alongside the better-recognized psychological and dispositional factors, to understand client engagement in the context of reentry.